Soft-mechanochemical synthesis of monodispersed BaZrO3 sub-microspheres: Phase formation and growth mechanism - Charoonsuk, Thitirat; Vittayakorn, Naratip (My University, 2017)
Current technological and scientific challenges have encouraged the search for a simple and energy-efficient method to synthesis fine product particles with desirable morphology and properties. The submicro-spheres of perovskite barium zirconate (BaZrO3) in this study were synthesized successfully via the soft-mechanochemical method under ambient conditions, without surfactants or any capping agents. The synthetic mechanism model was proposed as being time-dependent. The hydrolysis, nucleation (crystallization) and growth of particles via Ostwald ripening were discussed deeply. Mechanical energy not only afforded a local high temperature to activate the chemical reaction and diffusion rate of particles, but also prevent aggregation and agglomeration by homogeneous mechanical stirring. Nevertheless, as-prepared BaZrO3 powders exhibited properties of photoluminescence (PL) with green emission from lattice formation defects. Dielectric properties and the quality factor (Q-factor) were investigated as well. It was notable that the soft-mechanochemical method can provide a high yield and enable work that is environmentally friendly.
Keywords: BaZrO3; Soft-mechanochemical synthesis; Sub-microspheres